The Impact of the Making Music Game on Early Childhood Physical-Motor and Cognitive Development - Ida Marina Harahap; Khadijah Khadijah; Ridho Ansyah (Journal of Islamic Education Students (JIES), 2024)
This study aims to measure the impact of the Making Music game in supporting the physical-motor and cognitive development of early childhood children. The research method used is a quantitative approach with a quasi-experimental design, testing the effect of the Making Music game on these developmental aspects. The study employs a pre-test and post-test design with a Paired Samples Test Design, comparing pretest and posttest scores after the children were exposed to the Making Music game. The study population consists of 22 children in class B at RA AN-NIDA’, with 12 boys and 10 girls. The sample was determined using total sampling. The results show that the Making Music game has a positive impact on the fine motor, gross motor, and cognitive development of the children, as evidenced by the increase in pretest and posttest scores. This study is expected to contribute to the development of enjoyable and effective play-based learning methods for early childhood growth and development.